Lebetus patzneri (Teleostei: Gobiidae), a new goby species from the Balearic Islands, western Mediterranean, with first records of Lebetus guilleti (Le Danois, 1913) from this area and Norway, and with notes on its biology - Schliewen, Ulrich K.; Kovačić, Marcelo; Cerwenka, Alexander F.; Svensen, Rudolf; Ordines, Francesc (Zootaxa, 2019)
A new goby species, Lebetus patzneri sp. nov. (Teleostei: Gobiidae) is described based on two preserved and two photographed specimens collected from two circalittoral bottom locations off the Balearic Islands, western Mediterranean. It differs from the one or both other Lebetus species by each of following characters: P 15–16; D2 segmented fin rays 7–8; snout slightly larger than eye diameter; eyes small, 23.3–25.5% of head length; body height low, body depth at pelvic fin 14.9–16.4%; lips thick, giving mouth a broad, almost rectangular shape in dorsal and lateral view; minute black “pepper” spots on predorsal area, dorsum, flanks and caudal peduncle, visible in fresh and preserved specimens; the most of the caudal peduncle similarly colored as the lateral area below D2, reddish or brown. We further report first records of Lebetus guilleti (Le Danois, 1913) from Norway and the Balearic Islands, and observations of its conspicuous courtship behavior (“D1 waving”), and coloration including the first description of its red fluorescence pattern.